2022
DOI: 10.1097/mcg.0000000000001672
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic Significantly Impacts Pregnancy Planning and Mental Health of Women With Inflammatory Bowel Disease

Abstract: Background and Goals: The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted daily life, particularly in those with inflammatory bowel disease (IBD). We aimed to determine the impact of the pandemic on the pregnancy planning and mental health of women with IBD. Methods: Women with IBD (age 18 to 45 y) were asked to complete anonymous surveys on the impact of the COVID-19 pandemic on pregnancy planning and mental health symptoms such as stress (Perceived Stress Scale), depression (Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…23 Moreover, anxiety is an additional risk factor that intervenes in neonatal development in a number of ways. 37,[51][52][53] This research has shown the multiple circumstances that can have an impact on the levels of fear and anxiety of women with a pregnancy in progress, becoming determinants of their state of mind.…”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, anxiety is an additional risk factor that intervenes in neonatal development in a number of ways. 37,[51][52][53] This research has shown the multiple circumstances that can have an impact on the levels of fear and anxiety of women with a pregnancy in progress, becoming determinants of their state of mind.…”
Section: Discussionmentioning
confidence: 99%